Indonesian Interpretation of the Qur’an on Khilāfah: The Case of Quraish Shihab and Yudian Wahyudi on Qur'an, 2: 30-38 - M Djidin; Sahiron Syamsuddin (Al-Jami'ah Research Centre, 2019)
Today the issue of building al-khilāfah al-islāmīyah (Islamic Caliphate) has been raised by Hizbut Tahrir Indonesia (HTI). One of its arguments is that it is obligatory, because Qur’an, 2:30 mentions the term khalīfah. However, this argument has been questioned by many Muslim scholars. Some of them are Quraish Shihab and Yudian Wahyudi. In this article a comparative study is conducted in such a way we can provide readers with a ‘direct’ comparasion between Shihab’s and Wahyudi’s thoughts. The emphasis of their differences is shown more clearly than their similarities. Some important points that are discussed here are their interpretations of Qur’an, 2: 30-38. After analyzing their statements expressed in their writings and interviews, we have found that both have the same idea that Qur’an, 2: 30 does not talk about the Islamic Caliphate, and therefore, it cannot be used as an argument for its building. We have also found that they have exegetical differences that might refer to the fact that Shihab has much emphasis on the ‘historical meaning’ of the verses, whereas Wahyudi prefers their ‘significance’ for human beings.[Wacana khilafah Islam di Indonesia menguat seiring dengan kehadiran Hizbut Tahrir Indonesia (HTI). Salas satu argumen mereka adalah adanya istilah khalīfah dalam Qur’an, 2: 30. Namun argument tersebut justru menjadi persoalan bagi pemikir muslim lainnya, dua diantaranya Quraish Shihab dan Yudian Wahyudi. Dalam tulisan ini diharapkan pembaca dapat melihat secara langsung perbandingan dua pemikiran tersebut. Beberapa point penting yang diperdebatkan adalah tafsir ayat Qur’an, 2: 30-38. Berdasarkan analisis pada karya tulis dan wawancara, keduanya sama – sama menunjukkan bahwa ayat tersebut di atas tidak membahas al-khilāfah al-islāmīyah. Meskipun keduanya sependapat, masing-masing memberikan tekanan yang berbeda dimana Shihab lebih ke makna historis, sedangkan Wahyudi condong ke signifikasi bagi kemanusiaan.]